Mid-Term Follow-up of Minimally Invasive Multivessel Coronary Artery Bypass Grafting: Is the Early Learning Phase Detrimental?. Issue 2 (March 2017) - Rodriguez, Maria Lorena; Lapierre, Harry R.; Sohmer, Benjamin; Glineur, David; Ruel, Marc
Abstract : Objective: Minimally invasive coronary artery bypass grafting (MICS CABG) through a small left thoracotomy is a novel technique for surgical coronary revascularization, which is increasingly being adopted around the world. This study aimed to describe the characteristics and mid-term outcomes of a series of MICS CABG to identify areas for improvement. Methods: A prospective longitudinal study was performed on the 306 MICS CABG patients operated on by a single surgeon from 2005 to 2015. Minimally invasive coronary artery bypass grafting used a small left thoracotomy to enable coronary revascularization with a similar configuration to an open sternotomy technique, with left internal thoracic artery harvesting, and hand-sewn proximal radial/saphenous and distal anastomoses, under direct visualization. We compared patients who were operated on during the first and second halves of the series to ascertain the impact of a learning curve on outcomes. Results: The mean ± SD age was 62 ± 9 years, 87% were male, and 23% had three-vessel disease. Off-pump coronary artery bypass was performed in 80%, and the median number of grafts was 2 (range 1–4). Sternotomy conversion occurred in 3.3%, reoperation for bleeding in 2%, and unplanned, emergency CPB conversion in 1%. Superficial thoracotomy infection, atrial fibrillation, and left-sided pleural effusion requiring drainage were encountered in 2%, 4%, and 4%, respectively. There were no perioperative stroke, myocardial infarction, or death. At a mean ± SD follow-up of 2.8 ± 2.5 years, 97.4% of patients were free from major adverse cardiac and cerebrovascular events. Between the first and latter half of the series, there was a decrease in the rate of conversion to sternotomy (5.2%–1.3%, P = 0.05) and in the mid-term need for repeat revascularization (11% vs 2.6%, P = 0.03). Overall repeat revascularization rate was 2.5% per year. The intensive care unit and hospital lengths of stay (1.6 ± 1.5 vs 1.4 ± 0.9, P = 0.2, and 6.1 ± 2.6 vs 5.6 ± 1.8, P = 0.4) were not statistically different. Conclusions: Minimally invasive coronary artery bypass grafting can be safely initiated as a minimally invasive, multivessel alternative to open surgical coronary revascularization, with excellent mid-term results. Learning phase effects were not observed with regard to overall procedural safety, but rather in terms of improved freedom from conversion to sternotomy and from repeat revascularization.